The Impact of Internet Corporate Reporting on Market Performance: The Moderating Role of Woman on Board - Aisanafi, Yuannisa; Karjono, Marini (IJOSMAS, 2023)
This research investigates the impact of internet corporate reporting on market performance, with woman on board as moderating variable. This is quantitative research that uses 99 observations from banking companies listed in Indonesia Stock Exchange. Based on the analysis done using STATA software, it is proven that the internet corporate reporting has positive and significant impact on market performance. Moreover, the role of woman on board also gives positive and significant impact in the relationship between internet corporate reporting and market performance